Therapeutic doses of neostigmine, depolarising neuromuscular blockade and muscle weakness in awake volunteers: a double‐blind, placebo‐controlled, randomised volunteer study1. (21st August 2018) - Kent, N. B.; Liang, S. S.; Phillips, S.; Smith, N. A.; Khandkar, C.; Eikermann, M.; Stewart, P. A.
Summary: Neostigmine reverses non‐depolarising neuromuscular blockade, but may cause muscle weakness when administered after full recovery of neuromuscular function. We hypothesised that neostigmine in therapeutic doses impairs muscle strength and respiratory function in awake healthy volunteers. Twenty‐one volunteers were randomised to receive two doses of either intravenous (i.v.) neostigmine 2.5 mg with glycopyrrolate 450 μg (neostigmine group, n = 14) or normal saline 0.9% (placebo group, n = 7). The first dose was administered immediately after obtaining baseline measurements, and the second dose was administered 15 min later. All 14 volunteers in the neostigmine group received the first dose, mean (SD) 35 (5.8) μg.kg −1, but only nine of these volunteers agreed to receive the second dose, 34 (3.5) ?g.kg ‐1 . The primary outcome was hand grip strength. Secondary outcomes were train‐of‐four ratio, single twitch height, forced expiratory volume in 1 s, forced vital capacity, forced expiratory volume in 1 s/forced vital capacity ratio, oxygen saturation, heart rate and mean arterial pressure. The first dose of intravenous neostigmine with glycopyrrolate resulted in reduced grip strength compared with placebo, −20 (20) % vs. +4.3 (9.9) %, p = 0.0016; depolarising neuromuscular blockade with decreased single twitch height, −14 (11) % vs. −3.8 (5.6) %, p = 0.0077; a restrictive spirometry pattern with decreased predicted forced expiratory volume in 1 s, −15 (12) % vs. −0.47 (3.4) %, p = 0.0011; and predicted forced vital capacity, −20 (12) % vs. −0.59 (3.2) %, p < 0.0001 at 5 min after administration. The second dose of neostigmine with glycopyrrolate further decreased grip strength mean (SD) −41 (23) % vs. +1.0 (15) %, p = 0.0004; single twitch height −25 (15) % vs. −2.5 (6.6) %, p = 0.0030; predicted forced expiratory volume in 1 s −23 (24) % vs. −0.7 (4.4) %, p = 0.0063; and predicted forced vital capacity, −27.1 (22.0) % vs. −0.66 (3.9) %, p = 0.0010. Train‐of‐four ratio remained unchanged (p = 0.22). In healthy volunteers, therapeutic doses of neostigmine induced significant and dose‐dependent muscle weakness, demonstrated by a decrease in maximum voluntary hand grip strength and a restrictive spirometry pattern secondary to depolarising neuromuscular blockade.